Effect Of Lead Acetate (Pb(Ch3coo)2 On The Growth Of Marine Microalgaes Chlorella vulgaris (Beijerink, 1890) - Jeheskiel, Aprilisa Viony; Kemer, Kurniati; Mantiri, Desy Maria Helena; Paulus, James; Rompas, Rizald M.; Khreekhoff, Renny (Sam Ratulangi University, 2022)
Microalgae are single-celled microorganisms, forming colonies and are very commonly found in large waters such as seas, lakes, rivers, and swamps. The purpose of this study was to determine the growth and density of microalgae Chlorella vulgaris in a controlled container with the administration of lead acetate at different concentrations. Cell growth of Chlorella vulgaris with samples of marine microalgae Chlorella vulgaris from culture containers. At the beginning of the exponential phase, the microalgae were given lead acetate in 3 containers with concentrations of 30 ppm, 50 ppm, 80 ppm, and control/without treatment. The results showed that the growth of Chlorella vulgaris cells with lead acetate administration experienced unstable growth compared to those without lead acetate administration (control).Keywords: Microalgae; Chlorella vulgaris; Culture; Lead AcetateAbstrakMikroalga merupakan mikroorganisme bersel satu, membentuk koloni dan sangat banyak dijumpai di perairan besar seperti pada laut, danau, sungai serta perairan payau. Tujuan dari penelitian ini adalah untuk mengetahui pertumbuhan dan kepadatan mikroalgaÂ Chlorella vulgaris dalam wadah terkontrol dengan pemberian timbal asetat pada konsentrasi yang berbeda. Pertumbuhan sel Chlorella vulgaris denga Sampel mikroalga laut Chlorella vulgaris berasal dari wadah kultur. Pada awal fase eksponensial, mikroalga diberikan timbal asetat ke dalam 3 wadah dengan konsentrasi 30 ppm, 50 ppm, 80 ppm serta kontrol/tanpa perlakuan. Hasil penelitian menunjukkan bahwa pertumbuhan sel Chlorella vulgaris dengan pemberian timbal asetat mengalami pertumbuhan yang tidak stabil dibandingkan tanpa pemberian timbal asetat (kontrol).Kata kunci: Mikroalga;Â Chlorella vulgaris;Â Kultur; Timbal Asetat